Effect of enzymatic supplementation in productive parameters of guinea pigs of (Synthetic Line P 0.625) - Bernaola Rodriguez, Ferggie (2021)
The aim of this study was to evaluate the effect of the supplementation of an enzymatic complex in integral diets for guinea pigs in the growing phase on productive performance. In total, 54 male guinea pigs (Synthetic line P 0.625) were used and submitted to a diet free of the enzyme complex (T1), and two experimental ones, one with 0.1% (T2) and the other with 0.2% (T3) of enzyme complex evaluated between two weeks of age (weaning) and after rearing (nine weeks old). It was statically evaluated and there were found no significant difference between treatments in relation to final body weight, weight gain, feed intake and feed conversion; and it was reported the weekly average of percentage of dairy dry matter intake by body weight.